Development of a new characteristic parameter – waveform index of finger blood volume pulse. (16th December 2016) - Wu, Wenjie; Yang, Lin; Zhang, Song; Hao, Dongmei; Yang, Yimin; Li, Xuwen; Wu, Guanghui; Zhang, Lei; Luo, Zhichang
Abstract: Background: Finger blood volume pulse (F-BVP) contains abundant human cardiovascular system information, including information regarding circulation in the heart, blood vessel function, and the microcirculation system. Pulse waveform analysis is a method for analyzing F-BVP. Methods and results: A new parameter of F-BVP, called waveform index (WI), was extracted, defined, subsequently compared between groups of different cardiovascular function, and compared with age and systolic blood pressure. WI values of the negative and positive groups were 0.209 ± 0.066 ( p  < .001) and 0.305 ± 0.066 ( p  < .001), respectively. The classification threshold value of WI was 0.24, revealing a sensitivity of 77%, a specificity of 68% and a classification accuracy of 73%. The odds ratio (OR) was 7.164, indicating that subjects with WI >0.24 had a 7.164 times greater risk of suffering from cardiovascular disease than of not suffering from cardiovascular disease. Age and systolic blood pressure had consistent correlation with WI, in addition, WI had the same trend with age and systolic blood pressure. Conclusion: Because WI of F-BVP was determined according to only F-BVP waveform and increases in age and systolic blood pressure, different values of WI represent different cardiovascular physiological conditions. To a certain extent, the changes of WI reflect the changes of human cardiovascular function. Therefore, WI has the potential to be widely used in disease screening and clinical practice.